Hubungan Pola Asuh Orang Tua dan Pengaruh Gadget Terhadap Perkembangan Kognitif Siswa SD Inpres Bangkala III Kota Makassar - Merry Merry; Perawati Bte Abustang; Waddi Fatimah; Satriawati Satriawati (Publikasi Indonesia, 2022)
The Relationship between Parenting Parenting Patterns and the Effect of Gadgets on Cognitive Development of Students at SD Inpres Bangkala III Makassar City, which was supervised directly by Nurses Bte Abustang and Waddi Fatimah. This study aims to determine the effect of parenting and the influence of Gadgets on the cognitive development of students at SD Inpres Bangkala III Makassar City. This research uses Ex Post Facto method with quantitative approach. The population used in each class is III, IV, and V SD Inpres Bangkala III Makassar City which consists of 159 students. The sample in this study were fifth grade students consisting of 26 students. The results of the study used descriptive statistical analysis, parenting patterns were 28.19, while the influence of Gadgets was 20.69 and students' cognitive development was 32.0769. Analysis of the requirements for the normality test results of parenting is 0.261, while the influence of Gadgets is 0.120, and students' cognitive development is 0.275 > 0.05 (normally distributed). There is an effect of parenting and Gadgets on the cognitive development of the students of SD Inpres Bangkala III Makassar City.